OXIDATION-REDUCTION RELATIONS IN BASIC MAGMA: A CASE FOR HOMOGENEOUS EQUILIBRIA - Carmichael I.S.E.; Ghiorso M.S. (My University, 1986)
Published analyses of Fe2O3 and FeO in basaltic glassy lavas allow their equilibrium oxygen fugacities to be calculated. These values are plotted relative to NNO (nickel-nickel oxide oxygen buffer) at the same temperature (1200°C), so that the relativefO2, ΔNNO, becomes essentially independent of temperature. For 61 submarine tholeiitic lavas from the Pacific, ΔNNO lies between FMQ (fayalite-magnetite-quartz oxygen buffer) and NNO, whereas 95 glassy lavas from the Atlantic show a greater range, and can be more oxidised than NNO; in both oceans, alkali types have higher ΔNNO.In contrast, subaerial glassy lavas, dominated by those of Kilauea, are more reduced than the Pacific submarine lavas, and cluster between FMQ and W-Mt (wüstite-magnetite oxygen buffer). This subaerial reduction, first recognised by Anderson and Wright [1], is caused by SO2 degassing. The iron redox state of Kilauea subaerial and submarine glassy lavas can vary considerably, but as found in other submarine lavas, their sulphur redox state varies more. We conclude that the iron and sulphur redox systems of tholeiitic liquids, in combination, could act as a self-regulating internal oxygen reservoir, constraining a cooling liquid to the constant relative oxygen fugacity observed in well characterised liquid lines of descent.A second experimentally verifiable hypothesis is offered, namely that Fe2O3 in natural silicate liquids is very compressible. Thus magmas equilibrating at great depth (∼30–50 kbar) with a solid mantle assemblage of low relativefO2 (intrinsic measurements) would have a higher iron redox state than those equilibrating with shallow mantle sources at the same relativefOs. The redox states of basic magmas, ascending isochemically and involving Fe and S, could therefore be a depth indicator to their source regions.